PEMBELAJARAN BERBASIS LINGKUNGAN (Realisasi Ekotologi Intergralistik di Perguruan Tinggi) - Ali Halidin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
Duality is one reality (God One), in this universe consisting of only two common types, God and not God; The Creator and the Creature. The first type has only one member namely Allah SWT. He alone is the eternal God, the transcendent Creator. There is nothing similar to Him, while the second is the composition of God's created being made up of nature and all its contents, the first impossible, but the second extinction, the extinction of nature and of life. Ideality is a natural power that synergizes with the power of human understanding and belief. Understanding is used to understand the will of God through observation and on the basis of creation, the will of the ruler who must be actualized in space and time, participate in world activities and create desired change. Understanding the application of recognition of knowledge of truth as a principle of knowledge. Tawheed is the recognition that God is, is and is One. The recognition that the truth can be known and man is able to achieve it, through the process of learning (understanding). This study focuses on natural studies and conceptions in interpreting Islamic ecology among students and students in Indonesia, and emphasizes the need to be serious. The concept of Islamic ecology is an insistence on science, to be preserved and developed. Practically its presence along with Islamic doctrine brought by Muhammad Saw. Slowly but surely, all aspects of human life, can not be separated from the process of improvement and refinement. Both with regard to simple things such as the purification of self from impurities (unclean), to matters concerning environmental sanctification, even corpses (dead). This paper describes, there is no problem that is beneficial to human beings, unless all the problems are related even in accordance with the teachings of Islam, but sometimes this issue is not a concern by all mankind, even consider it trivial. Considering Islam only regulates ubudiyah problems ranging from praying, fasting zakat, alms and pilgrimage. This can be seen from the lack of awareness in disposing of waste in its place. Or the lack of awareness of hygiene and consistent in maintaining the environment. The effort of learning by prioritizing the values of environmental virtue is very necessary to be done early, start learning at Kindergarten level, up to college. This form of business is not only limited to habituation, but more than that, in the form of awareness and love that is formed in the minds of every Muslim, because the love of nature, is a form of love to Allah SWT.